The Transformation of Indonesia's Criminal Law System: Comprehensive Comparison between the Old and New Penal Codes - Nugraha, Roby Satya; Rohaedi, Edi; Kusnadi, Nandang; Abid, Abid (Reformasi Hukum, 2025)
The old Indonesian Penal Code (KUHP), inherited from the Dutch Penal Code (Wetboek van Strafrecht), is considered no longer relevant to the values of justice and the needs of contemporary Indonesian society. This study aims to compare the criminal law system and the criminal justice system under the new Penal Code, as well as to conduct an in-depth analysis of the fundamental legal principles embedded in both the old and new KUHP. The research employs a normative juridical method with comparative legal approach, analyzing the legal norms within both codes to identify substantial changes. The result indicate that the new KUHP reflects a paradigm shift from a repressive legal system to a more humanistic and restorative model, emphasizing human rights protection, gender-based justice, and the recognition of modern crimes such as sexual violence and organized crime. It also introduces alternative sanctions, including community service and rehabilitation, as efforts to support social reintegration. In conclusion, the new KUHP is not merely a replacement of the old KUHP but a progressive step toward a more inclusive and contextually appropriate criminal law system. Comprehensive implementing regulations and ongoing evaluation are essential to ensure its effective application and real impact on society.